Self-Regulation for Learning in the Context of Brazilian Education: An Integrative Review (Revista Lusófona de Educação, 2025)
Students with self-regulated learning are motivated and autonomous, create strategies and set goalsto achieve their goals. They have control of emotions and can change the path used to carry out a certain activity when necessary. These characteristics are described in different national and international surveys. To identify how Brazilian researchers approach the concept of self-regulation for learning in Basic and Higher Education, an integrative review was carried out based on the documents available in the Digital Library of Theses and Dissertations. Until November/2019, twenty-two theses were collected that met the inclusion and exclusion criteria defined for the study. The analysis was based on six categories: definition of the concept, contributions from cited authors related theory, interaction possibilities, relevance to education, and fallacy related to the concept. Zimmerman is the most used author to support localized concepts. The Social Cognitive Theory stands out in the works analyzed, which explains the perspective that the interaction between teachers and students and between students and their peers can promote self-regulation in the teaching and learning processes. Finally, the works emphasize the importance of this process so that students are responsible or your learning and building their own knowledge.